TECHNICAL AND VOCATIONAL EDUCATION TRAINING (TVET) FOR STUDENTS WITH LEARNING DISABILITIES: IMPLEMENTATION IN COMMUNITY COLLEGES IN MALAYSIA (Proceedings of International Conference on Special Education, 2015)
All children are unique and are influenced by cultural, linguistic, intellectual, psychological, medical, social and economic factors. These factors create a need for a varied educational environment that provides for, and accommodates, each child’s strengths and areas of needed improvement. Students classified as having a learning difficulty are a heterogeneous group and have a wide variety of characteristics, ranging from academic difficulties to cognitive and social-emotional problems (Kraayenord and Elkins, 1990). They face barriers in Technical and Vocational Education and Training (TVET) Institution. Community College in Malaysia offers Technical and Vocational Education and Training (TVET) courses to post-secondary students and provide lifelong learning to individuals and local communities to improve the quality of life. The core function of Community College in Malaysia is to provide pre-employment training or pre-employment education to school leavers who can contribute to the development of the country. TVET for Students with Learning Disabilities in Malaysia Community College faces several challenges since majority of the content of the courses are practical-based. The main purpose of this paper is to review best practices in the implementation of Special Skills Certificate in teaching and learning as well as to carry out research on its effectiveness in Community College that integrates the students, environment and lecturers who have expertise in TVET. The study carried out in 7 Community Colleges in Malaysia that offer Special Skills Certificates. The target population of the study consisted of the lecturers who are teaching this programme. Observation and interview were used as the instruments for data collection. Results showed that the environment variable, lecturers and students themselves play an important role in the success of the Special Skills Certificate in community colleges. Findings also indicated the challenges in delivery techniques for students with learning disabilities. Therefore, this paper recommends adding the number of lecturers or welltrained persons with disabilities to the Special Program Certificates and also to provide assistance to students. There is also the need for Community Colleges to upgrade the facilities and increase the number of Special Skills Certificate in community colleges throughout the country so that these opportunities can be enjoyed by all students with learning disabilities.